Pendidikan Kewarganegaraan Sebagai Upaya Penguatan Etika Sosial Peserta Didik - Susi; Ramdhani, Ahmad; Halimah, Neneng; Agustin, Putri Wulan; Hidayat, Wahyu (Universitas Cokroaminoto Yogyakarta, 2025)
Civic Education (PKn) plays a strategic role in shaping the character of the nation’s young generation to become faithful, virtuous, democratic individuals who are able to live harmoniously amidst diversity. In the era of globalization and rapid digital technology development, Civic Education not only teaches citizens’ rights and responsibilities but also instills moral values, ethics, and critical thinking skills. Through active learning approaches such as discussions, simulations, case studies, and social projects, Civic Education can enhance students’ national awareness, social ethics, and leadership skills. The challenges faced in implementing Civic Education in the digital era include infrastructure gaps, low levels of technological literacy among teachers and students, and the lack of quality digital resources. This literature study emphasizes the importance of strengthening social ethics, Pancasila values, and 21st-century skills in Civic Education so that the young generation is prepared to become responsible, tolerant, and globally minded citizens.